Peningkatan Keterampilan Menyimak Peserta Didik Menggunakan Teknik Dictogloss di Kelas V UPTD SD Negeri 01 Andiang Kabupaten 50 Kota - Putra, Fazila; Adrias, Adrias (TSAQOFAH, 2025)
The low listening skills of elementary school students are often attributed to conventional teaching approaches and the limited variety of techniques that promote active engagement and effective learning processes. Additionally, difficulties in processing auditory information negatively affect comprehension of orally delivered material. This study aims to describe the improvement of students' listening skills through the application of the Dictogloss technique. The research employed Classroom Action Research (CAR) across two cycles, involving the stages of planning, implementation, observation, and reflection. The subjects were 12 fifth-grade students at UPTD SD Negeri 01 Andiang, Lima Puluh Kota Regency. A mixed qualitative and quantitative approach was used. The results indicated a significant improvement in listening skills, with the average instructional module score increasing from 85.71% to 96.42%, the teacher performance aspect from 79.16% to 95.83%, and the student participation aspect from 75% to 95.83%. Students’ listening skills also improved from 74.29% in the first cycle to 90.23% in the second cycle. These findings affirm that the Dictogloss technique is effective in enhancing the listening abilities of elementary students. The study highlights the importance of employing innovative instructional techniques to strengthen auditory literacy competencies at the primary education level.